Implementation of an Internal Control System Based on Tri Hita Karana Culture in Fraud Prevention Efforts in Village Credit Institutions - Lisa, Kadek; Atmadja, Anantawikrama Tungga; Purnamawati, I Gusti Ayu (Dinasti Publisher, 2025)
Fraud in Village Credit Institutions or Lembaga Perkreditan Desa (LPD) often arises from weak supervision and low managerial professionalism. LPD Desa Adat Kesiman exemplifies effective fraud prevention through integrating the Tri Hita Karana philosophy into its Internal Control System. This study aims to examine the rationale, implementation, and impact of integrating Tri Hita Karana values into the Internal Control System. This qualitative ethnographic study explores the rationale, implementation, and impact of Tri Hita Karana integration in preventing fraud. Data were collected from the Head of LPD, Supervisory Board, employees, and community members using interviews, documentation, and artifact analysis, with validity ensured through triangulation and member checking. Findings show that Tri Hita Karana values strengthen moral and social control as well as public trust. The Parahyangan dimension manifests in spiritual practices; Pawongan in honesty, solidarity, and responsibility; and Palemahan in environmental awareness. Implementation includes integrity pledges, competent recruitment, technology use, SOP updates, structured communication, layered supervision, and profit allocation per regulations. This integration fosters ethical governance, financial service quality, innovation, and customer loyalty. Embedding Tri Hita Karana values enhances integrity, professionalism, and internal control effectiveness while preventing fraud through culturally rooted moral awareness and accountability.